Characteristics of greenhouse gas emissions from an anaerobic wastewater treatment system in a natural rubber processing factory. Issue 22 (2nd October 2019) - Tanikawa, Daisuke; Watari, Takahiro; Mai, Trung Cuong; Fukuda, Masao; Syutsubo, Kazuaki; Nguyen, Ngoc Bich; Yamaguchi, Takashi
ABSTRACT: Greenhouse gas (GHG) emissions from both open-type and closed anaerobic wastewater treatment systems in a natural rubber processing factory in Vietnam were surveyed. In this factory, wastewater was treated by an open-type anaerobic baffled reactor (OABR) that comprised 60 compartments. A part of the wastewater was fed to a pilot-scale up-flow anaerobic sludge blanket (UASB) reactor to enable a comparison of the process performance and GHG emission characteristics with those of the OABR. In the OABR, 94.4% of the total chemical oxygen demand (COD) and 18.1% of ammonia nitrogen was removed. GHGs emitted from the OABR included both methane and nitrous oxide. The total GHGs emitted from the OABR was 0.153 t-CO2 eq/m 3 -wastewater. Nitrous oxide accounted for approximately 65% of the total GHGs emitted from the OABR. By contrast, 99.6% of the methane emission and 99.9% of nitrous oxide emission were reduced by application of the UASB. However, the ammonia removal efficiency of the UASB was only 2.2%. Furthermore, Acinetobacter johnsonii, which is known as a heterotrophic ammonia remover, was detected only in the OABR. These results indicated that high nitrous oxide emissions were caused by denitrification in the OABR and that application of the closed anaerobic system could drastically reduce the emissions of both methane and nitrous oxide. GRAPHICAL ABSTRACT: